2016
DOI: 10.1017/jog.2016.118
|View full text |Cite
|
Sign up to set email alerts
|

A plot-scale study of firn stratigraphy at Lomonosovfonna, Svalbard, using ice cores, borehole video and GPR surveys in 2012–14

Abstract: ABSTRACT. Spatial heterogeneity of snow and firn properties on glaciers introduces uncertainty in interpretation of point and profile observations and complicates modelling of meltwater percolation and runoff. Here we present a study of the temporal and spatial dynamics of firn density and stratigraphy at the plot-scale (≈10 m × 10 m × 10 m) repeated annually during 2012-14 at the Lomonosovfonna icefield, Svalbard. Results from cores, video inspections in boreholes and radar grid surveys are compared. Ice laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
3
22
0
Order By: Relevance
“…Referenced to the glacier surface in April 2014 these depths correspond to 7, 9.1, and 11.3 m. The phenomena can be related to perched horizons with increased water content that have a horizontal extent less than the plot covered by our thermistor measurements (6×6 m). In April 2014 Marchenko et al (2017) found multiple ice layers at 7, 8, 9, and 10.8 m depth in three boreholes where the thermistor strings used in present study were installed afterwards. These ice layers could have acted as impermeable horizons and retained water which locally inhibited the cold wave penetration.…”
Section: Observed Snow and Firn Temperature Evolutionmentioning
confidence: 71%
See 3 more Smart Citations
“…Referenced to the glacier surface in April 2014 these depths correspond to 7, 9.1, and 11.3 m. The phenomena can be related to perched horizons with increased water content that have a horizontal extent less than the plot covered by our thermistor measurements (6×6 m). In April 2014 Marchenko et al (2017) found multiple ice layers at 7, 8, 9, and 10.8 m depth in three boreholes where the thermistor strings used in present study were installed afterwards. These ice layers could have acted as impermeable horizons and retained water which locally inhibited the cold wave penetration.…”
Section: Observed Snow and Firn Temperature Evolutionmentioning
confidence: 71%
“…yr −1 (Van Pelt et al, 2014;Wendl et al, 2015). Subsurface temperature measurements at Lomonosovfonna during summer season were carried out in 1965 (Zinger et al, 1966), 1980(Zagorodnov and Zotikov, 1980, and more recently by Marchenko et al (2017). While in Marchenko et al (2017) the focus was on subsurface density and stratigraphy, in this study the analysis concentrates on the subsurface temperature evolution.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…The front of Nordenskiöldbreen has retreated by 15-35 m/a since the end of the Little Ice Age, but retreat rates have been negligible since ∼2002 as the glacier is retreating on land (Allaart, 2016;Rachlewicz et al, 2007). Nordenskiöldbreen is a polythermal glacier ("type b" in Blatter & Hutter, 1991), with temperate conditions in the accumulation zone due to deep meltwater percolation and refreezing (Marchenko et al, 2016(Marchenko et al, , 2017Vega et al, 2016), and cold near-surface ice in the ablation area (Van Pelt et al, 2012). Nordenskiöldbreen is a polythermal glacier ("type b" in Blatter & Hutter, 1991), with temperate conditions in the accumulation zone due to deep meltwater percolation and refreezing (Marchenko et al, 2016(Marchenko et al, , 2017Vega et al, 2016), and cold near-surface ice in the ablation area (Van Pelt et al, 2012).…”
Section: Study Areamentioning
confidence: 99%